Functional reorganization and taxonomic shifts in the symbiotic microbiota of the temperate soft coral Eleutherobia rubra under heat stress - Kim, Jeong-A; Jo, Yejin; Hwang, Sung-Jin; Oh, Chulhong; Yang, Hyun-Sung; Lim, Jae Kyu; Woo, Seonock (Frontiers in Marine Science, 2025)
IntroductionGlobal ocean warming is known to disrupt interactions between corals and their symbiotic microbiota; however, the temporal sequence of structural and functional changes within microbial communities under thermal stress remains poorly understood. In this study, we investigated the microbial response of the soft coral Eleutherobia rubra following short-term heat exposure.MethodsColonies of E. rubra were collected near Eoyudo, Korea, exposed to short-term thermal stress (26 °C for 24 hours) alongside controls (16 °C). 16S rRNA gene sequencing was conducted to assess taxonomic shifts. Predicted functional profiles were inferred using PICRUSt2, and microbial community changes were evaluated through alpha and beta diversity analyses, LEfSe, and correlation analyses.ResultsThe overall taxonomic composition showed minimal change, with noticeable variations restricted to rare taxa. In contrast, functional predictions revealed consistent and pronounced reorganization of metabolic potential, characterized by increased core metabolic activities and a decline in several stress associated pathways. Beta diversity and LEfSe analyses indicated limited taxonomic shifts, but more distinct functional differentiation. Correlation analyses further suggested that specific microbial taxa may be driving these functional changes.DiscussionOur findings suggest that in E. rubra, functional restructuring of the microbiome precedes taxonomic shifts during 24h of heat stress exposure. These observation represent microbial responses under the experimental conditions and provide a basis for future studies on longer-term dynamics.